2010
DOI: 10.3851/imp1514
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity and tolerability of amdoxovir with zidovudine in a randomized double-blind placebo-controlled study in HIV-1-infected individuals

Abstract: The combination of amdoxovir plus zidovudine appeared synergistic with reduced VL variability. This combined therapy, including the use of a lower zidovudine dosage, warrants further development for the therapy of HIV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…DXG was evaluated in the presence of AZT in macrophages (42,43). The cellular accumulation of DXG-TP and AZT-TP were unaffected by coincubation (Table 2), supporting similar findings in activated lymphocytes and lending further incentive for the development of this drug combination (44).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…DXG was evaluated in the presence of AZT in macrophages (42,43). The cellular accumulation of DXG-TP and AZT-TP were unaffected by coincubation (Table 2), supporting similar findings in activated lymphocytes and lending further incentive for the development of this drug combination (44).…”
Section: Discussionmentioning
confidence: 57%
“…Since AZT and DXG are not cross-resistant, AZT can prevent the emergence of the K65R mutation, and in combination, the two drugs are synergistic in vitro and in humans (42). DXG was evaluated in the presence of AZT in macrophages (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility of developing an AMDX and ZDV coformulation is currently being explored, since this combination demonstrates synergy in vitro and at least additivity in vivo (36) against HIV-1 and prevents the selection of K65R mutation/ TAMs in primary human lymphocytes (40). A previous simulation study suggested that the ZDV dose may be reduced from 300 mg b.i.d.…”
Section: Discussionmentioning
confidence: 99%
“…Amdoxovir [(Ϫ)-␤-D-2,6-diaminopurine dioxolane (AMDX or DAPD)] is a guanosine nucleoside analogue being developed for the treatment of HIV-1 infections (23,31,47). AMDX is in advanced phase 2 clinical development under a U.S. Food and Drug Administration Investigational New Drug Application and has been administered safely to over 200 persons in seven human phase I/II trials (23,31,36,47,50). AMDX is a prodrug which undergoes rapid oral absorption in humans and other species and is deaminated by the ubiquitous enzyme adenosine deaminase to 9-(␤-D-1,3-dioxolan-4-yl)guanine (DXG) (4,16,35).…”
mentioning
confidence: 99%
See 1 more Smart Citation